2015
DOI: 10.1177/1756287215612962
|View full text |Cite
|
Sign up to set email alerts
|

The role of neoadjuvant therapy in the management of locally advanced renal cell carcinoma

Abstract: Abstract:In the past decade, the armamentarium of targeted therapy agents for the treatment of metastatic renal cell carcinoma (RCC) has significantly increased. Improvements in response rates and survival, with more manageable side effects compared with interleukin 2/interferon immunotherapy, have been reported with the use of targeted therapy agents, including vascular endothelial growth factor (VEGF) receptor tyrosine kinase inhibitors (sunitinib, sorafenib, pazopanib, axitinib), mammalian target of rapamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…Neoadjuvant target therapy may also lead to disease progression and make some patients suffer from adverse effects [22]. In our study, we found that neoadjuvant targeted therapy was safe for RCC patients in terms of side effects and surgeries.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Neoadjuvant target therapy may also lead to disease progression and make some patients suffer from adverse effects [22]. In our study, we found that neoadjuvant targeted therapy was safe for RCC patients in terms of side effects and surgeries.…”
Section: Discussionmentioning
confidence: 63%
“…The effectiveness of neoadjuvant therapy in reducing tumor size [19] and reducing tumor complexity [20] was proved. However, the therapeutic effect of neoadjuvant therapy on RCC patients with tumor thrombus is still controversial and neoadjuvant therapy might be less encouraged for RCC patients with tumor thrombus [21,22], while no study investigated whether neoadjuvant therapy could increase the survival outcomes for RCC patients with tumor thrombus so far. Thus, this work is the first research which focuses on survival benefits of neoadjuvant therapy to explore the value of it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the current era of TT, NT strategies have regained the attention of oncologists, and several trials of NT for RCC and mRCC have recently been completed or are ongoing (567). Some trials have established the safety and response rates of NT with several agents, but there is no consensus in the literature regarding the effectiveness, safety, and clinical utility of NT (8). Therefore, the possible or conceivable indications for neoadjuvant TT now include the treatment of 1) large unresectable advanced tumors to facilitate surgery, 2) imperative indications to enable a nephron-sparing procedure, and 3) high-level vena cava thrombi involvement to achieve downsizing and facilitate the use of simpler surgical techniques that are associated with lower morbidity rates.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence in the literature demonstrates the potentially expanding role of preoperative targeted therapy with tyrosine kinase inhibitors in the management of locally advanced RCC [31]. Traditionally, systemic therapy has shown limited usefulness, and aggressive radical surgical resection with IVC thrombectomy remains the standard of care in appropriate candidates.…”
Section: Surgical Strategiesmentioning
confidence: 99%